Web-based program for sexual and reproductive health education of immigrant women: A scoping review protocol. - Suhyun Kim; Aeri Jang (PLoS ONE)
Developing web-based education sexual and reproductive health (SRH) programs for immigrant women is crucial. This scoping review aims to provide basic data for developing more advanced programs by examining web-based educational program literature. This review considers web-based SRH education programs for adult immigrant women and focuses on their characteristics, instructional strategies, and outcome evaluations. Data will be extracted following the Minimum Initial Service Package (MISP) and Kirkpatrick level and summarized to show future-oriented results while documenting web-based approach evidence for educating immigrant women on SRH. It is expected to provide information for web-based education programs to meet the MISP and develop various evaluation methods. As such, the findings can be used to determine the direction and level of SRH education.